DETERMINATION OF PUNISHMENT FOR AGGREGATION OF CRIMINAL OFFENCES - Persidskis, Ainārs (Administrative and Criminal Justice, 2015)
The purpose of the article is to identify the problems related to the determination of punishment for several criminal offences, find the problems and offer possible solutions. If all criminal offences, constituting the aggregation of criminal offences are criminal violations or less serious crimes, the final punishment shall be determined, including the lesser punishment within the more serious or also completely or partially adding together the punishments imposed. With this regulation, the purpose of punishment is not achievable. The people, who commit two or more criminal offences does more moral, physical and material damage, these people, showing a negative attitude toward the State, society and the individual’s interests. These people think that they don’t have to respect the rights of others, so these people must be judged negatively, than people, who do one criminal offence. The final punishment for two or more criminal offences should be more severe in comparison to the punishment that the Court ordered the guilty person, who committed a one criminal offence.